ENT 530 Social Media Portfolio: Jointhree / Muhammad Nizar Amat Yahaya - Amat Yahaya, Muhammad Nizar (2021)
Jointhree offers ready stock furniture for customers, such as bed furniture, bean bag, bench, cabinet, coffee table, lounge chair, rack, sofa, sofa bed, stool, study table, trolley and many more. There is a lot of furniture that gives high satisfaction to the users. Our customers are identified customers are all classes of users who want modern and minimalist furniture. I am also targeting for those who are starting to decorate the house, newlyweds and bachelors. At the same time the customer can get this furniture in two ways namely self-acquisition and home delivery or COD. Jointhree will be sold in Banting, shah Alam and Klang valey. The area is densely populated with housing and development areas. The majority of the population in this area is married, married and single. Nowadays, people like to decorate the house to look more luxurious and beautiful but at the same time they want cheap furniture and install their own. Therefore, Jonthree furniture is one of the modern and minimalist furniture design. Jointhree Social Media Platform is to emphasize the quality, design, promotion and price of the product. Jointhree offers cheap but worthwhile so that everyone can enjoy a harmonious home atmosphere. As a result, I developed many interesting strategies for my clients. Jointhree is run by myself and assisted by my friends. We will be responsible for all tasks. The furniture we provide is direct from the factory because we use high quality goods. Jointhree will provide the best for customers throughout Malaysia especially Banting, Shah Alam and klang valey areas.